Literature and the littoral in South Africa: reading the tides of history - Geustyn, Maria Elizabeth (Department of English Language and Literature, 2022)
This thesis explores representations of the littoral in South African literature. It analyses literature published in three broad historical periods with the specific focus on the littoral as a setting from which authors imagine histories differently, often as a corrective, to challenge and wrestle with the racialized categorization of bodies in space. Littoral settings are present throughout the history of South African literature and, when placed on a linear, progressive timeline, feature as a place of first encounters, a site of segregation, and the unmaking of these boundaries. This thesis argues, however, that sequencing representations of the littoral according to this model would subsume histories by those without the power to control official narratives, or whose histories are not well represented in official archives, under rigid nation-based paradigms of typical western historiography. By employing Kamau Brathwaite's theory of “tidalectics” as a method, metaphor and model, I conduct a recursive reading of the littoral's presence in South African literature to show that littoral moments resonate with each other across different historical moments. As such, tidalectics attend to multiple temporalities in a more open, fluid way. I argue that this manner of attending to history surfaces from and sits alongside formal historiography, gently disrupting its premises by offering alternative models for recognising and recording marginal narratives. The primary texts for this thesis include Portuguese expansionist texts, novels by prominent South African authors such as Olive Schreiner, Nadine Gordimer, Peter Abrahams, Zoë Wicomb, Lewis Nkosi, and Yvette Christiansë, and a poetry collection by Douglas Livingstone. In these texts, the littoral is presented as a space which is governed by the spatial politics of that era, but also challenges them, playing a valuable part in constructing spatial politics, and in turn racial politics, in South Africa. A tidalectic reading of these literatures therefore demonstrates that the littoral allows for a different spatio-temporal approach to the long history of social injustice in South Africa.